Perancangan Aplikasi Chatting Symmetric Encryption dengan Metode SDLC - Andi, Andi; Jesson, Jesson; Kevin, Kevin; Lie, Melvin; Yulianto, Andik (Telcomatics, 2023)
Chat Application is an application that allow people to communicate with each other without face-to-face meetings or time issue. To design a well-functioning chat application, this study was conducted using the Software Development Life Cycle (SDLC) method for designing chat application. Apart from that, this study will be using the Python programming language, the PyMySQL module used to connect python to the database, and the Tkinter module is used as a tool in this study to create a Graphical User Interface (GUI) for chat application, and not to mention this study will be using Symmetry Encryption Cryptography to perform encryption and decryption of user chat data.